Dimensionen der Wahrnehmung von Varianz - Joachim Gessinger (Linguistik Online, 2017)
The SiN-project data corpus delivers an empirical foundation for the study of different dimensions in the perception of variation as “divergence from common usage” (H. Paul). In addition to the “objective” linguistic data (Produktionsdaten) obtained through biographical interviews, informal chats with relations and friends (Tischgespräche) as well as tasks to explore the variational repertoire of the informants, the corpus also displays results of the elicitation of linguistic knowledge and language attitudes obtained through specific testing methods, in which the purpose was to evaluate non-standard language features as to their salience, the situational dependence and norm adequacy and to trigger metalinguistic comments. In order to give plausible qualitative and quantitative evidence about the regional diversity of perception and linguistic variation in Northern Germany I will show the interdependence between the realization of phonological features divergent from spoken standard and perceptional dispositions of the informants which indicate the sociopragmatic function of phonological and morphosyntactic variation.